Prayer paper production facility layout redesign using systematic layout planning method and CRAFT - J Tampubolon; L D Agoestine Simangunsong; M D Agustina Sibuea; A C Sembiring and A Mardhatillah (International Journal of Science, Technology & Management, 2020)
Abstract. The facility layout is a strategic design that is used for a long time. All manufacturing industries must pay attention to the right layout to increase the productivity of the industry. A prayer paper manufacturing industry located in the Tanjung Morawa area, Medan has an error in the placement of raw materials and the placement of production machines, so that the distance from the temporary warehouse to the printing and cutting work stations is far apart, causing high material handling costs. Seeing these problems, research was carried out to improve the layout of the facilities and redesign. The method used for this research is Systematic Layout Planning (SLP), which is one of the methods used to regulate a workplace in a factory by using two areas with high frequency and logical relationships with each other. And the Computerized Relative Allocation of Facilities Technique (CRAFT) Algorithm is a repair program, which is a program that looks for optimal design by making gradual improvements to the layout. CRAFT evaluates the layout by interchanging departmental locations. Inputs required for the CRAFT algorithm include initial layout, data flow or frequency of movement, cost data per unit distance, and the number of departments that do not change or remain. The CRAFT method is usually applied using Quantitative Systems (QS) software. By comparing the layout between SLP and CRAFT, the optimal result is obtained using the SLP method by reducing the distance between departments by 1.407 meters or a distance efficiency of 39.91%.